2016
DOI: 10.2196/medinform.4577
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Electronic Medical Record Use on Practice-Based Population Health Management: A Mixed-Method Study

Abstract: BackgroundPractice-based population health (PBPH) management is the proactive management of patients by their primary care clinical team. The ability of clinics to engage in PBPH and the means by which they incorporate it in a clinical setting remain unknown.ObjectiveWe conducted the Canadian Population Health Management Challenge to determine the capacity and preparedness of primary care settings to engage in PBPH using their existing medical record systems and to understand the complexities that may exist in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…24,28,38,40,44 Our current review of the evidence suggests that population based approaches to diabetes care have significant potential for continuing to improve diabetes care and outcomes, and are well-aligned with current policy initiatives to increase both the accountability and patient-centeredness of the U.S. health care system. However, our review of the literature also found that there are a limited number of published evaluations of specific diabetes population care approaches, and those that are published may not have the level of programmatic detail required for dissemination into other settings.…”
Section: Recommendations For Future Research and Policymentioning
confidence: 89%
See 1 more Smart Citation
“…24,28,38,40,44 Our current review of the evidence suggests that population based approaches to diabetes care have significant potential for continuing to improve diabetes care and outcomes, and are well-aligned with current policy initiatives to increase both the accountability and patient-centeredness of the U.S. health care system. However, our review of the literature also found that there are a limited number of published evaluations of specific diabetes population care approaches, and those that are published may not have the level of programmatic detail required for dissemination into other settings.…”
Section: Recommendations For Future Research and Policymentioning
confidence: 89%
“…27 Recent research suggests that when clinicians and practices use electronic health records, as opposed to traditional paper-based records, they enhance their ability to provide high-quality diabetes population care. 2829 …”
Section: Key Components Of Diabetes Population Managementmentioning
confidence: 99%
“…To clarify the results, informal interviews were conducted with six head of clinics (specialists) in the three surveyed hospitals. Following the method recommended by Vaghe et al [52], these heads were randomly selected based on their experience in using an EHR system. Discussion of the ndings thus begins with an overview of the results, followed by supports from real practices acquired from the interviews and prior literature.…”
Section: Discussionmentioning
confidence: 99%
“…Routinen aus ambulanter Betreuung und Versorgung haben genau dieses Potential. Erst kürzlich konnte eine amerikanische Arbeitsgruppe zeigen, wie die intelligente Nutzung primärärztlicher Routinedaten auch positiv die Gesundheitsversorgung auf Gemeindeebene beeinflussen kann [29]. Dafür muss jedoch in Deutschland die Nutzung solcher Daten technisch und organisatorisch wesentlich erleichtert werden.…”
Section: Diskussionunclassified